At-C-RNA database, a one-stop source for information on circRNAs in Arabidopsis thaliana in a unified format. (11th November 2021) - Nowis, Katarzyna; Jackowiak, Paulina; Figlerowicz, Marek; Philips, Anna
Abstract: Circular RNAs (circRNAs) are a large class of noncoding RNAs with functions that, in most cases, remain unknown. Recent genome-wide analysis of circRNAs using RNA-Seq has revealed that circRNAs are abundant and some of them conserved in plants. Furthermore, it has been shown that the expression of circRNAs in plants is regulated in a tissue-specific manner. Arabidopsis thaliana circular RNA database is a new resource designed to integrate and standardize the data available for circRNAs in a model plant A. thaliana, which is currently the best-characterized plant in terms of circRNAs. The resource integrates all applicable publicly available RNA-seq datasets. These datasets were subjected to extensive reanalysis and curation, yielding results in a unified format. Moreover, all data were normalized according to our optimized approach developed for circRNA identification in plants. As a result, the database accommodates circRNAs identified across organs and seedlings of wild-type A. thaliana and its single-gene knockout mutants for genes related to splicing. The database provides free access to unified data and search functionalities, thus enabling comparative analyses of A. thaliana circRNAs between organs, variants and studies for the first time. Database URLhttps://plantcircrna.ibch.poznan.pl/